A non-premixed reactive volatilization reactor for catalytic partial oxidation of low volatility fuels at a short contact time. Issue 4 (2nd March 2021) - Lin, Ying; Li, Xuesong; Twigg, Martyn V.; Northrop, William F.
Abstract : This work presents a novel non-premixed opposed-flow reactive volatilization reactor that simultaneously vaporizes and partially oxidizes low volatility liquid hydrocarbons at a short contact time (<12 ms). Abstract : This work presents a novel non-premixed opposed-flow reactive volatilization reactor that simultaneously vaporizes and partially oxidizes low volatility liquid hydrocarbons at a short contact time (<12 ms). In the reactor, a catalyst-coated metal mesh is placed interstitially between an air duct and a liquid pool. Low-volatility fuels are evaporated by radiative and convective heating and combine at local stoichiometry determined by the axial location of the mesh. Experiments were conducted with n -dodecane at different local molar carbon-to-oxygen ratios (C/O) and inlet airflow. Platinum and rhodium coated mesh substrates were the active materials for performing partial oxidation. A 1D opposed-flow similarity model based on the canonical opposed-flow combustion solution was created to simulate the axial temperature and species concentration along the reactor centerline. Results show that the reactor vaporized and converted n -dodecane to reformed products at a global molar carbon-to-oxygen ratio (C/O)g of up to 3.46. However, the local mixture depended on mesh axial position, with (C/O)mesh ranging from 0.2 to 3.94 for platinum and 0.31 to 4.97 for rhodium. It was found that the local stoichiometry at the mesh surface plays a more important role than the global one since no gas-phase reactions occurred outside the mesh region. Overall, our work demonstrates that non-premixed catalytic reactive volatilization is a promising technique to investigate fundamental concepts in hydrocarbon reforming and can offer insights into designing practical short-contact time reactors that can have high conversion and selectivity but low surface carbon deposition tendency at high C/O.